Interleukin-33 promotes invasiveness of human ovarian endometriotic stromal cells through the ST2/MAPK/MMP-9 pathway activated by 17β-estradiol - Ta-Chin Lin; Kai-Hung Wang; Kuo-Hsiang Chuang; An-Pei Kao; Tsung-Cheng Kuo (Elsevier, 2021)
Objective: Endometriosis is an estrogen-dependent, benign, and chronic gynecological disorder occurring in women of reproductive age. Although the pathogenesis of endometriosis is poorly understood, implantation theory indicates that viable endometrial cells shed from the endometrium into the pelvic peritoneum or ovaries, possibly through retrograde menstruation, and then reattach, invade, and damage other tissues. Interleukin (IL)-33, a new member of the IL-1 superfamily, is mainly upregulated by stromal cells following proinflammatory stimulation. Matrix metalloproteinases (MMPs) are involved in the degradation and reconstruction of the extracellular matrix. MMP-9 participates in the pathogenesis of endometriosis by promoting the invasion of endometriotic cells. This study investigated the effect of IL-33 on the cell invasion ability of and MMP-9 expression in human stromal cells derived from ovarian endometrioma (hOVEN-SCs). Materials and methods: We isolated hOVEN-SCs from human ovarian endometrioma. Gene expression was analyzed using the Illumina Human WG-6 v2 Expression BeadChips microarray platform and through reverse transcription-polymerase chain reaction. Cell migration and invasion were examined by performing the transwell chamber assay. Results: We found that 17β-estradiol could increase the expression of IL-33 and ST2 through the estrogen receptor pathway in hOVEN-SCs. Moreover, IL-33 upregulated MMP-9 expression in and enhanced the invasion ability of hOVEN-SCs through the ST2/MAPK signaling pathway. Our results showed that MMP-9 expression was essential for IL-33-induced cell invasion. Conclusion: Our main finding is that 17β-estradiol could increase IL-33 expression through the estrogen receptor pathway and activate MMP-9 expression in and invasion ability of hOVEN-SCs through the IL-33/ST2/MAPK signaling pathway. The results of this study and further related studies may provide new strategies for the prevention and treatment of endometriosis.